Biochemical Attributes of Mithun Semen - Perumal, P. (International Journal of Bio-resource and Stress Management, 2017)
The present study was designed to estimate the biochemical attributes of good and poor quality mithun semen. Fifty ejaculates (twenty five each for good and poor quality ejaculates) were collected from matured mithun bulls. Biochemical attributes such as alkaline phosphatase (ALP), acid phosphatase (ACP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactic acid dehydrogenase(LDH), calcium (Ca), magnesium (Mg), zinc (Zn), chloride, citric acid, total seminal plasma protein (TSPP), inorganic phosphorous (IP), fructose and cholesterol in sperm were estimated. The result revealed that these attributes were varied significantly (p<0.05) between the good and poor quality ejaculates. Good quality ejaculates has significantly (p<0.05) higher ALP, ACP, LDH, Ca, Mg, Zn, citric acid, TSPP, IP, fructose and cholesterol and has significantly (p<0.05) lower value in chloride concentration than in poor quality ejaculates. Moreover, there was positive correlation among the biochemical attributes such as ALP, ACP, LDH, Ca, Mg, Zn, CA, TSPP, IP, fructose, cholesterol and these attributes were negatively correlated with AST, ALT and chloride in both good and poor quality ejaculates. It was concluded that most of the biochemical attributes were higher in good quality than in poor quality ejaculates, indicated that former has structural stability than the latter that leads to former sperm has higher functional structures to move faster and in forward direction.